2010
DOI: 10.1007/s12088-010-0038-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of toxigenic strains of Aeromonas species in foods by a multiplex PCR assay

Abstract: Aeromonas hydrophila and other aeromonads are ubiquitous organisms found in meat, vegetables, drinking water and various other food items. They cause diarrhea and extra-intestinal infections in normal and immunocompromised patients. The aim of the study was to develop a multiplex PCR assay for the detection of virulenceassociated genes of Aeromonas including hemolysin (hlyA), aerolysin (aerA), glycerophospholipid-cholesterol acyl transferase (GCAT) alongwith a 16S rRNA gene. Internal amplifi cation control (IA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…hydrophila. On the other hand the MPCR assay developed by Balakrishna et al (2010) could detect 50 CFU/g of A. hydrophila in fish samples based on aerolysin and hemolysin genes with overnight incubation in alkaline peptone water (APW-A) broth and the detection limit of the assay was 5 pg with pure genomic DNA. As the amplification of bacterial DNA directly from food complexes by PCR often give poor yield, enrichment of the samples prior to PCR has been recommended by many workers (Merino et al 1995).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…hydrophila. On the other hand the MPCR assay developed by Balakrishna et al (2010) could detect 50 CFU/g of A. hydrophila in fish samples based on aerolysin and hemolysin genes with overnight incubation in alkaline peptone water (APW-A) broth and the detection limit of the assay was 5 pg with pure genomic DNA. As the amplification of bacterial DNA directly from food complexes by PCR often give poor yield, enrichment of the samples prior to PCR has been recommended by many workers (Merino et al 1995).…”
Section: Resultsmentioning
confidence: 99%
“…2). The multiplex PCR assays developed by Nam and Joh (2007) and Balakrishna et al (2010) were specific for Aeromonas , as they did not amplify the selected virulent genes in E . coli, Vibrio cholerae, Salmonella typhimurium , Staphylococcus aureus and Proteus vulgaris.…”
Section: Resultsmentioning
confidence: 99%
“…Since, laboratory procedures for isolation and identification of aeromonads are laborious and time consuming, several virulence associated genes have been targeted for detection of potentially pathogenic aeromonads by PCR including hemolysin, cytolysin, aerolysin genes (Wang et al, 2003;Aslani and Hamzeh, 2004;Balakrishna et al, 2010). Earliest report on development of PCR assay to detect aerolysin gene in A. hydrophila is from Pollard et al (1990) with a detection limit of 1 ng of total nucleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Yogananth et al (2009) found that 50% of the Aeromonas isolated from fish samples collected from local market in Chennai, India were positive for A. hydrophila. Balakrishna et al (2010) detected A. hydrophila from 8.5% of raw fish samples procured from different location in Mysore, India using a MPCR assay targeting virulence associated genes of Aeromonas including hlyA, aerA, GCAT, along with 16S rRNA gene. However, Bin Kingombe et al (2004) found that 59% of raw food samples were contaminated with Aeromonas harbouring virulent genes and the contamination of raw foods with Aeromonas was proportionally high in raw shrimps (56%) and fish (75%).…”
Section: Discussionmentioning
confidence: 99%